ANALISA SISTEM PELELANGAN PENGADAAN BARANG DAN JASA PEMERINTAH KALIMANTAN TIMUR SECARA ELEKTRONIK - SETYAWAN, ARIK (KURVA S JURNAL MAHASISWA, 2014)
The auction is procurement conducted openly (publicly) with the announcement widely through the print media and the official notice board (where possible through electronic media) so that the wider community / business interested and sprinkle qualifications to apply. Auctions held by the government, especially the Department of Public Works East Kalimantan province are now carried on electronically.With the aim to provide solutions to improve information technology and open systems through LPSE or procurement of goods and services on line through the Internet. Held system with procurement of goods and services electronically, it is necessary to know the identification of the efficiency of the system so that the relationship between service users and service providers can be concluded.The method used to collect data by way of questionnaires and interviews to the service user and service provider. While the method of data analysis using SPSS version 19.00.From the analysis it can be concluded with the procurement of goods and services are conducted electronically by the government, especially the Department of Public Works East Kalimantan province that does not produce a positive relationship between the service user by the service provider.